1969
DOI: 10.25071/1488-5182.36579
|View full text |Cite
|
Sign up to set email alerts
|

Parody of the Gay Games: Gender Performativity in Sport

Abstract: In this article, the authors suggest that within the confines of conventional sporting contexts (including the Gay Games), politicized gender parody is difficult to achieve. They ruminate on the possibilities of queering sport and gender within a new, hypothetical sporting event for the Gay Games: drag Debra Shogan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In this regard, building a (politicized) fat body already falls under the designation of bodybuilding as sport as technology of the self, and fat bodybuilding is already a sport, even recognizing inbuilt paradoxes of conformity (Chapman 1997;Markula 2003;Wesely 2001). These views are not identical to but are consistent with the use of sport as a postmodern disruption (see Pronger 1998) and with seeing new sporting activities as intentional parodies (see Shogan and Davidson 1999). Rather, the intention to engage in postmodern critique and parodic disruption, even through sport (as seen in the Fattylympics), is itself an application of Foucault's technology of the self-intersecting with sport in a way relevant to fat activists.…”
Section: Why Fat Bodybuilding?mentioning
confidence: 95%
See 1 more Smart Citation
“…In this regard, building a (politicized) fat body already falls under the designation of bodybuilding as sport as technology of the self, and fat bodybuilding is already a sport, even recognizing inbuilt paradoxes of conformity (Chapman 1997;Markula 2003;Wesely 2001). These views are not identical to but are consistent with the use of sport as a postmodern disruption (see Pronger 1998) and with seeing new sporting activities as intentional parodies (see Shogan and Davidson 1999). Rather, the intention to engage in postmodern critique and parodic disruption, even through sport (as seen in the Fattylympics), is itself an application of Foucault's technology of the self-intersecting with sport in a way relevant to fat activists.…”
Section: Why Fat Bodybuilding?mentioning
confidence: 95%
“…The Fattylympics ultimately relies on (Judith) Butlerian parodic performance, which has been effectively utilized as a culturally disruptive tool, especially with regard to gender/queer activism (J. G. Butler 1990Butler , 1993cf. Chalkin 2016;Hester and Walters 2016;Shogan and Davidson 1999). Here, as Monaghan, Colls, and Evans (2015) explained, "Fattylympics illustrated the possibility of claiming a public space for resisting the dominant anti-fat ethic of sport and physical activity, constructing an alternative value set for active bodies and critically understanding the relationship between fat and health" (117).…”
Section: Fat Activismmentioning
confidence: 99%
“…Most, but certainly not all, interviewees were reluctant to consider a more radical and subversive approach to sporting events within the Games, instead taking the view that they were an opportunity to 'prove to straights that we can be as athletic as they can' (Jack, 43). To incorporate elements of drag or camp into the sporting programme (Shogan & Davidson 1999), it was generally believed, was to risk undermining its sporting credibility amongst heterosexuals. Several interviewees suggested that, if some sports practices needed to be challenged, the initiative should come from within the governing body itself.…”
Section: Playing the Field: 'I've Never Been A Football Person'mentioning
confidence: 99%